QoS aware evaluation model supporting service correlation in manufacturing cloud service composition - Xiaolan XIE; Lanying ZENG; Qinghai ZHAI (Tongxin xuebao)
In order to select better quality of manufacturing cloud services that meet the demand of manufacture to complete manufacturing tasks in coordination, a QoS aware evaluation model supporting service correlation was proposed based on interface correlation, business entity correlation, and statistics correlation, aiming at the impact of QoS accuracy on combination screening.The cooperation time, KULC and IR parameters were introduced, and the historical information was used to predict and dynamically adjust the statistical association QoS changes to ensure timeliness.The feasibility of the proposed method is verified by an example analysis, and the experimental results show that the method can provide a more realistic solution for the service demander.